PERFORMA HIDRAULIKA AMBANG DAN PINTU KLEP UNTUK SKENARIO REWETTING: KAJIAN PEMODELAN AWAL KANAL SUKA PINDAH SUAKA MARGASATWA PADANG SUGIHAN: Hydraulic Performance of Overflow Weirs and Flap Gates for Peatland Rewetting: A Preliminary Modeling Study of Suka Pindah Canal Padang Sugihan Wildlife Reserve - Santoso, Kurniawan Putra; Wignyosukarto, Budi Santoso; Jayadi, Rachmad (Jurusan Teknik Sipil Fakultas Teknik Universitas Mataram, 2025)
The Padang Sugihan Wildlife Reserve is facing the threat of fires, which have a detrimental impact on the ecosystem of the Sumatran Elephant habitat. To mitigate this risk, this research aims to evaluate the hydraulic efficiency of overflow weir and flap gates as interventions for peatland restoration in the Suka Pindah Canal. 1D HEC-RAS modeling indicates that without control structures, tidal fluctuations at the estuary are ineffective in maintaining soil moisture. The scenario with a flap gate at the Suka Pindah Canal estuary can increase the volume of water by up to 115% compared to the existing condition, but this water structure requires well maintenance. In contrast, an overflow weir that is 1.5 times wider than the flap gate scenario proves to be more efficient, with a 72% better increase in water volume than the flap gate, as well as a simpler design. Further analysis shows that the upstream area of the canal, consisting of low-elevation land (natural ponds), has the potential to double the water retention capacity in the canal and land. These findings indicate that control structures are effective for rewetting efforts.